The Healing Quilt - Brunstetter, Wanda E. (Uhrichsville, Ohio : Shiloh Run Press, 2014)
Amish newlyweds Lamar and Emma Yoder Miller seek warmer weather in Sarasota, Florida, and have purchased a small house in the Pinecraft community. But Emma wishes her days had more purpose than leisurely walks on the beach. Before long she is sending back home for her supplies amd advertising a quilting class. Wounded and hurting people have a knack for finding their way to Emma's classes for some quilting therapy: Jennifer, a pregnant new mom; Mike, a charter boat owner; Erika, a wheelchair-bound teen; Kim, a waitress; Noreen, a newly retired widow; and BJ, an artist facing illness. God will use Emma and Lamar on each of their journeys toward healing frayed hearts. And when Jan Sweet visits from Indiana, a romantic twist is unexpectedly added to the class dynamics.
"Return of the Half-stitched Amish Quilting Club"--Cover.
Keywords: Amish -- Fiction; Quilting -- Fiction; Christian fiction